KATA GANTI ORANG DALAM BAHASA INGGRIS DAN BAHASA SELARU (SUATU ANALISIS KONTRASTIF) - Oratmangun, Rosa (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2015)
ABSTRACT This research attempts to identify and classify personal pronouns in English and Selaru language. The data are taken from interviewing some informants (native speakers) who was born in Selaru and understand the language and can interact effectively. The identified data are analyzed according to the concept of Bloomfield and then contrast them by using Lado’s concept. In analyzing the data, the writer uses descriptive method. The problems of this research ore focused on what are the personal pronouns in terms of form and function in English and Selaru language and what are the similarities and differences of personal pronouns in terms of form and function in English and Selaru language. The aims of the research are to identify and classify personal pronouns in English and Selaru language and to find out the similarities as well as dissimilarities of personal pronouns in both languages in terms of form and function. The results of this research shows that English and Selaru language has similarities and dissimilarities. Similarities in English and Selaru language which has the form of the first person, second, third, both singular and plural and dissimilarities in English and Selaru language namely: in English has object, possessive pronoun and third person singular neutral,whereas in selaru language not found. Key words: Personal Pronouns In English and Selaru Language, Contrastive Analysis.